2006
DOI: 10.1093/jxb/erl199
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of OsHKT1, OsHKT2, and OsVHA are differentially regulated under NaCl stress in salt-sensitive and salt-tolerant rice (Oryza sativa L.) cultivars

Abstract: Under NaCl-dominated salt stress, the key to plant survival is maintaining a low cytosolic Na(+) level or Na(+)/K(+) ratio. The OsHKT1, OsHKT2, and OsVHA transporter genes might play important roles in maintaining cytosolic Na(+) homeostasis in rice (Oryza sativa L. indica cvs Pokkali and BRRI Dhan29). Upon NaCl stress, the OsHKT1 transcript was significantly down-regulated in salt-tolerant cv. Pokkali, but not in salt-sensitive cv. BRRI Dhan29. NaCl stress induced the expression of OsHKT2 and OsVHA in both Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
112
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 56 publications
7
112
0
Order By: Relevance
“…The tissue specificity of OsHKT2;1 expression presented in this study on the japonica rice 'Nipponbare' is consistent with the pattern previously reported in the same cultivar by Horie et al (2007) and overlaps with, but also differs slightly from, the expression patterns reported in indica rice varieties (Golldack et al, 2002;Kader et al, 2006). Our study also provides the first information on two other HKT transporters, OsHKT1;1 and OsHKT1;3.…”
Section: Expression Patterns and Roles In The Plantsupporting
confidence: 91%
See 1 more Smart Citation
“…The tissue specificity of OsHKT2;1 expression presented in this study on the japonica rice 'Nipponbare' is consistent with the pattern previously reported in the same cultivar by Horie et al (2007) and overlaps with, but also differs slightly from, the expression patterns reported in indica rice varieties (Golldack et al, 2002;Kader et al, 2006). Our study also provides the first information on two other HKT transporters, OsHKT1;1 and OsHKT1;3.…”
Section: Expression Patterns and Roles In The Plantsupporting
confidence: 91%
“…Information on tissue localization was available for three members of each HKT subfamily so far: AtHKT1;1 from Arabidopsis (Berthomieu et al, 2003;Sunarpi et al, 2005), OsHKT1;5 from rice (Ren et al, 2005), and McHKT1;1 from ice plant (Mesembryanthemum crystallinum; Su et al, 2003) for subfamily 1; TaHKT2;1 from wheat (Schachtman and Schroeder, 1994), OsHKT2;1 (Golldack et al, 2002;Kader et al, 2006;Horie et al, 2007), and OsHKT2;2 (Kader et al, 2006) from rice for subfamily 2. The whole set of data emphasized that HKT transporters are strongly expressed in tissues (root epidermis and cortex, xylem and phloem, vascular bundle regions) playing crucial roles in ion uptake or long-distance transport and redistribution in the plant.…”
Section: Expression Patterns and Roles In The Plantmentioning
confidence: 99%
“…Excess of Na + in the cytosol counteracts the optimal cytosolic Na + /K + ratio, and is recognized as K + deficiency. Inducing HKT1 under such K + deficiency conditions seems detrimental if the HKT1 protein were to be Na + -specific (Kader et al, 2006). Under salt stress, when cytosolic Na + concentration reaches a toxic level, plants activate highaffinity K + transporters for K + uptake that adjust cellular Na + /K + balance (Yao et al, 2010;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…LEA proteins are mainly low-molecular-weight (10-30 kDa) proteins involved in protecting higher plants from damage caused by environmental stresses, especially drought or dehydration [42][43][44][45]. HKT transporters mediate Na C unloading from the xylem under salinity stress, which prevents Na C overaccumulation in leaves, thereby protecting photosynthetic organs [46][47][48][49]. It is, therefore, tempting to speculate that the overexpression of OsDUF946.4 might have resulted in upregulated expression of LEA protein-like and HKT-transporter-like genes in E. coli, which could have led to the enhanced tolerance to drought and salinity.…”
Section: Expression Analysis Of Osduf946 Genes Under Various Stress Cmentioning
confidence: 99%